Factors associated with Chronic Kidney Disease of unknown aetiology (CKDu) in North Central Province of Sri Lanka: a comparative analysis of drinking water samples - D. G. Amara Paranagama; Muhammed A. Bhuiyan; Niranjali Jayasuriya (Applied Water Science, 2018)
Abstract Chronic Kidney Disease of unknown aetiology (CKDu) is a major health concern in North Central Province (NCP) of Sri Lanka. Anuradhapura and Polonnaruwa are the two most affected districts in NCP. This research was designed to identify main suspected CKDu causative agents in drinking water in NCP. Drinking water samples were collected from shallow wells of CKDu patients and non-patients in Anuradhapura and Polonnaruwa districts. They were tested for chemical ions: chloride, fluoride, nitrate, phosphate, calcium, magnesium, sodium, cadmium and arsenic. An analytical framework was developed to analyse water quality data using statistical methods, namely univariate analysis of variance (ANOVA) and Dunnett’s T3 post hoc test, Kruskal–Wallis (KW) and Mann–Whitney’s post hoc test, discriminant analysis, factorial analysis followed by reliability tests. ANOVA, KW and their post hoc tests were applied to show the significant differences at p < 0.05 in mean and median values of chemical constituents between CKDu patient and non-patient samples. Discriminant analysis was applied to show the degree of accuracy in original sampling groups. Factorial analysis was applied to identify the ion combinations in each group. A secondary set of data obtained from drinking water samples of CKDu endemic and non-endemic areas were also analysed independently using the same analytical techniques to compare the results.